Social jetlag in school students: evidence to suggest that sleep deprivation during work days is common. Issue 1 (2nd January 2017) - Chandrakar, Priti
Abstract: The present study investigated social jetlag in school students of the Raipur district of Chhattisgarh. The sample consisted of 919 school students from six different schools, age range 12–19 year, comprising of both males ( n  = 513) and females ( n  = 406). Two inventories, the 19-item MEQ and MCTQ (Munich Chronotype Questionnaire) were employed. Data analysis (SPSS) used t -test, Chi-square test, ANOVA, and correlation. The results revealed that 73.9% of the sample had social jetlag. There were significant effects upon social jetlag of chronotype, gender, and the use of an alarm clock. Owls were at a higher risk of having social jetlag. There was a significant positive correlation between the amount of social jetlag and the time spent watching television. From these results, it is concluded that there is prevalence of social jetlag, particularly among boys and those who use an alarm clock. The results also lead to the prediction that those school students with social jetlag will be predisposed to health hazards associated with it in the future. Thus it is recommended that school students must be provided with sleep education so that they understand the role of sleep on health and do not become sleep deprived.